Selection of Ruiru 11 hybrid sibs on raw coffee quality - Gichimu, Bernard M.; Gichuru, E. K.; Mamati, George E.; Nyende, A.B. (My University, 2012)
The economic value of Arabica coffee (Coffea arabica L.) is determined mainly by the yield potential, the size and shape of raw beans and beverage quality. Bean quality reportedly differ depending on the variety, environmental conditions and management practices. This study aimed at genetically improving raw bean quality of C. arabica cultivar Ruiru 11 through selection within the cultivar. The study also intended to measure the extent to which raw bean quality of Ruiru 11 is affected by the environment. Thirty four Ruiru 11 full-sibs grown in three locations in Kenya exhibiting strong edaphic and climatic differences were used for the study. The three sites were Mariene in Meru, Kisii and Koru. Rainfall amounts during various phases of berry development were used to explain the differences observed in discriminating abilities of the locations for raw bean quality traits. The results showed that beans of desirable AA and AB grades were obtained from Mariene where moderate moisture supply was received during berry expansion and bean filling stages rather than in high rainfall conditions. The best overall Ruiru 11 sibs were identified as R11-121, R11-93, R11-142, R11-52 and R11-71.
Keywords: coffee; Ruiru 11; Bean Grades; Kenya